Researching social life - Gilbert, G. Nigel (Los Angeles, Calif. : Sage Publications, 2008)
"Researching Social Life covers the whole range of methods from quantitative to qualitative in a down-to-earth and unthreatening manner. Internationally-renowned experts in the field have thoroughly expanded and updated this edition with new chapters and additional material on: mixed methods, participative action research, virtual methods, grounded theory, narrative analysis, searching for and reviewing literature, and refining the research question. Worked examples, case studies, discussion questions, project ideas and checklists are included throughout the book to help those new to research to engage with the material. Researching Social Life follows the `life cycle' of a typical research project, from initial conception through to eventual publication. Its breadth and depth of coverage make this an indispensable companion for students on social research methods courses in any discipline."--Publisher's Web site.
Conceptualizing social life / Geoff Cooper -- Research, theory and method / Nigel Gilbert -- Formulating and refining a research question / Nicola Green -- Searching and reviewing literature / Mary Ebeling and Julie Lamb -- Grounded theory and inductive research / Paul Hodkinson -- Participatory approaches to social research / Christina Silver -- Mixed methods / Victoria D Alexander, Hilary Thomas, Ann Cronin, Jane Fielding and Jo Moran-Ellis -- The Ethics of social research / Martin Bulmer -- Designing samples / Patrick Sturgis -- Questionnaires / Rosemarie Simmons -- Measuring attitudes / Mike Procter -- Focus groups / Ann Cronin -- Qualitative interviewing / Nigel Fielding and Hilary Thomas -- Ethnography / Nigel Fielding -- Using documents / Keith McDonald -- The Internet and research methods / Christine Hine -- Coding and managing data / Jane Fielding -- Analyzing survey data / Mike Procter -- Secondary analysis of survey data / Nick Allum and Sara Arber -- Computer Assisted Qualitative Data Analysis (CAQDAS) / Ann Lewins -- Narrative analysis / Sarah Earthy and Ann Cronin -- Conversation analysis and discourse analysis / Robin Wooffitt -- Analyzing visual materials / Victoria D. Alexander -- Writing about social research / Nigel Gilbert.
Includes bibliographical references (p. 516-538) and index.
Keywords: Sociology -- Methodology; Sociology -- Research